PENGARUH KARAKTERISTIK PEKERJAAN DAN LINGKUNGAN KERJA TERHADAP KEPUASAAN KERJA DENGAN MEDIASI MOTIVASI (Studi Pada Perawat UPT Puskesmas Rawat Inap Dinas Kesehatan Kabupaten Pati) - Tuk Rejeki, Widadi (Students Journal of Economic and Management, 2012)
The process of identification of the factors that affect the job characteristics and work environment becomes an important thing to consider in the improving job satisfaction and being an effective. It needs to be a concern for the organization due to low job satisfaction in an organization can interfere with the activity and productivity. The purpose of this study was to examine the influence of job characteristics and work environment on job satisfaction with the mediation of motivation. The research was conducted at the Health Center Inpatient Unit District Health Pati. Data on job characteristics, work environment, job satisfaction, and motivation is obtained through interviews using questionnaires to 102 respondents. Data were processed using analysis techniques with the help of Statistical Package for the Social Sciences (SPSS) The results showed job characteristics have a significant and positive effect on motivation,Â environment has a positive and significant effect on motivation, job characteristics have a positive and significant effect on job satisfaction, work environment has a positive and significant effect on job satisfaction and motivation has a negative effect and not significant impact on job satisfaction. Based on the results of hypothesis testing, the issues raised in this study can be answered. That job satisfaction is influenced by the characteristics of the job and work environment. Therefore, to increase job satisfaction, the management needs to make an effort to understand the characteristics of the work and making the environment better. Keywords: job characteristics, job environment, job satisfaction and motivation